2006
DOI: 10.1002/dvdy.20956
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA expression during chick embryo development

Abstract: MicroRNAs (miRNAs) are small, abundant, noncoding RNAs that modulate protein abundance by interfering with target mRNA translation or stability. miRNAs are detected in organisms from all domains and may regulate 30% of transcripts in vertebrates. Understanding miRNA function requires a detailed determination of expression, yet this has not been reported in an amniote species. High-throughput whole mount in situ hybridization was performed on chicken embryos to map expression of 135 miRNA genes including five m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
135
1
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(144 citation statements)
references
References 38 publications
7
135
1
1
Order By: Relevance
“…Subsequent high throughput whole mount in situ hybridization of chick embryos showed that 21 of these miRNAs, including let-7a and miR-10b, -18b, and -363, were present in the limb primordia beginning around Hamburger-Hamilton stage 14. Among them, miR-10b showed high level expression in limb bud from stage 18 through at least stage 24 (25). The chicken ortholog of the C. elegans lin-41 gene was also identified as being expressed in the developing chick limb (26).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Subsequent high throughput whole mount in situ hybridization of chick embryos showed that 21 of these miRNAs, including let-7a and miR-10b, -18b, and -363, were present in the limb primordia beginning around Hamburger-Hamilton stage 14. Among them, miR-10b showed high level expression in limb bud from stage 18 through at least stage 24 (25). The chicken ortholog of the C. elegans lin-41 gene was also identified as being expressed in the developing chick limb (26).…”
mentioning
confidence: 98%
“…Dicer deficiency in chondrocytes was found to reduce the proliferating pool of chondrocytes, leading to severe skeletal growth defects and premature death in mice. However, although several recent reports have indicated that miRNAs are critical to the regulation of chondrocyte proliferation and differentiation during skeletal development (25,28), the precise roles of miRNAs in the chondrogenic differentiation of limb mesenchymal cells have not yet been fully established. In this study, we show that miR-221 is a key modulator in the chondrogenic differentiation of chick limb mesenchymal cells and identify the Slug protein as a relevant target of miR-221.…”
mentioning
confidence: 99%
“…In addition, we have observed that MSCs and fibroblasts share similar microRNA expression profiles, indicating that microRNAs might not play such significant roles in either MSC-or fibroblast-specific functions, as observed in other biological processes, including embryo development (Darell et al 2007), carcinogenesis (Calin and Croce 2006), apoptosis (Cheng et al 2005), viral infection (Sullivan and Ganem 2005), and hematopoietic stem cell differentiation (Chen et al 2004). A notable exception to the homologous microRNA pattern shared by MSCs and fibroblasts has been found in mir-335 whose expression has been measured to be about 44-fold higher in MSCs than in fibroblasts.…”
Section: Discussionmentioning
confidence: 92%
“…Using various experimental methods, certain miRNAs were continuously reported in recent studies in the field of animal embryogenesis [26,27,28,29,30]. During the implantation period, potential regulators of endometrial receptivity include miRNAs [31].…”
Section: Discussionmentioning
confidence: 99%